Techno-functional properties, dough rheology and bread quality of flours from infrared and microwave heat-treated bambara groundnuts grains - Emmambux, Mohammad Naushad (University of Pretoria, 2023)
Thesis (PhD (Food Science))--University of Pretoria, 2023.